Serial five-membered lactone ring ions in the treatment of Alzheimer's diseases-comprehensive profiling of arctigenin metabolites and network analysis - Yanan Li; Yanan Li; Xianming Lan; Shaoping Wang; Yifang Cui; Yifang Cui; Shuyi Song; Hongyan Zhou; Hongyan Zhou; Qiyan Li; Long Dai; Jiayu Zhang (Frontiers Media S.A., 2022)
Arctigenin is a phenylpropanoid dibenzylbutyro lactone lignan compound with multiple biological functions. Previous studies have shown that arctigenin have neuroprotective effects in Alzheimer's disease (AD) models both in vivo and in vitro; however, its metabolism in vivo has not been studied. Most traditional analytical methods only partially characterize drug metabolite prototypes, so there is an urgent need for a research strategy that can fully characterize drug metabolites. In the present study, ions fishing with a serial five-membered lactone ring as a fishhook strategy based on ultrahigh-performance liquid chromatography-Q-Exactive Orbitrap mass spectrometry (UHPLC-Q-Exactive Orbitrap MS) was utilised to characterise the metabolism of arctigenin, and the establishment of this strategy also solved the challenge of creating a comprehensive metabolic profile of neolignan. Based on the proposed strategy, a total of 105 metabolites were detected and characterised, 76 metabolites of which were found in rats and 49 metabolites in liver microsomes. These metabolites were postulated to be produced through oxidation, reduction, hydrolysis, and complex reactions. Subsequently, network pharmacology was utilized to elucidate the mechanism of arctigenin and its main metabolites against Alzheimer's disease, screening 381 potential targets and 20 major signaling pathways. The study on the comprehensive metabolism of arctigenin provides a holistic metabolic profile, which will help to better understand the mechanism of arctigenin in the treatment of Alzheimer's disease (AD) and also provide a basis for the safe administration of arctigenin.